زواج القاصرات في عرف ولاية كانو بنيجيريا : دراسة فقهية تقويمية - صالح، عثمان ثاني (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The objective of this research his to study the girl -child marriage in the custom of kano state Nigeria, and the prapractice of marrying girls before attending pubepuberty by supplying relrelevant provisions from the Noble Qur'an and sunnah and the ijma, ( consensus) among jurists. Cases of child-bride in kano state are common and have stirred concerns from the shari,ah and health perspectives. The researcher adopted indutive assessment approaches by consulting the leading literary sources of the subject matter of the topic. It also conducted a case study using structured interview with the shari,ah scholars, medical docters and data on the causes, problems and solutions to the issue. The major findings is that girl child marriage may cause some health problems to such girl during pregnancy and at birth, and also malnutrition right from childhood is one major factor causes an extremely young brige incapable of discharging her marriage duties. It has caused a black eye on the shariah which has accused of condoning the practice of child bride.